Pembuatan Dextran Secara Fermentasi - Karsini Karsini (Balai Besar Kimia dan Kemasan, 1987)
Dextran is a polysaccharide synthesized by bacteria, including those belongingto the genera of Leuconostoc, Streptobacter. or related forms. Its principal utility now lies in its ability to serve as a blood plasma volume expander.Dextran's chemical and physical properties depend upon both the strain of micro organism employed, and the environmental conditions imposed upon the bacterium during growth or the reaction conditions imposed upon the bacterium during growth or the reaction conditions where an enzymatic method of dextran production is employed.Leuconostoc and Streptococcus species convert sucrose to dextran and fructose primarily. Acetobacter species convert dextrin to dextran, and its by product fructose thistransformation is mediated by an enzyme, dextran sucrase. Its· readily obtainedextracellularly from suitable strains of Leuconostoc mesenteroides propagatedunder appropriate conditions.